Delivery of Nanoparticles across the Intestinal Epithelium via the Transferrin Transport Pathway - Jing M. Yong; Julia Mantaj; Yiyi Cheng; Driton Vllasaliu (MDPI AG, 2019)
The aim of this study was to probe whether the transferrin (Tf) transport pathway can be exploited for intestinal delivery of nanoparticles. Tf was adsorbed on 100 nm model polystyrene nanoparticles (NP), followed by size characterisation of these systems. Cell uptake of Tf and Tf-adsorbed NP was investigated in intestinal epithelial Caco-2 cells cultured on multi-well plates and as differentiated polarised monolayers. Tf-NP demonstrated a remarkably higher cell uptake compared to unmodified NP in both non-polarised (5-fold) and polarised cell monolayers (16-fold difference). Application of soluble Tf significantly attenuated the uptake of Tf-NP. Notably, Tf-NP displayed remarkably higher rate (23-fold) of epithelial transport across Caco-2 monolayers compared to unmodified NP. This study therefore strongly suggests that the Tf transport pathway should be considered as a candidate biological transport route for orally-administered nanomedicines and drugs with poor oral bioavailability.